Social survey reportage: Context, narrative, and information visualization in early 20th century American journalism - Anderson, C.W. (Journalism, 2017)
This article takes a historical approach to the analysis of changes in the gathering and display of documents and data by journalists. It stands as an attempt to tease out the underlying epistemological changes implied by these transformations. The transition from the 19th to the 20th century would see the rise of the so-called survey movement, itself tied to the emergence of the progressive movement and concomitant with the growth of new techniques for collecting and visualizing social data. Alongside the emergence of the social survey, and oddly related to it in a number of intriguing ways, this time period would also see the invention of public relations as a technique of press management. To this end, this article chronicles the social movement known as the ‘Men and Religion Forward Movement’, discussing its pioneering combination of data collection, information display, and aggressive publicity strategies in service of the cause of social reform. The article examines the materiality of the Men and Religion Forward Movement’s information collection procedures, its charts, graphs, and other display devices, and the processes by which these ‘representations of the collective’ did or did not manifest themselves in newspaper coverage of the movement.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDY0ODg0OTE2NjU3NTI3